The frequency and etiology of anemia among children 6-16 years of age in the southeast region of Turkey - Koç, Ahmet; Kösecik, Mustafa; Vural, Hüseyin; Erel, Özcan; Ataş, Ali; Tatlı, M. Mansur (The Turkish Journal of Pediatrics, 2000)
The frequency and etiology of anemia were investigated in 2,913 children between six and 16 years of age in Şanlıurfa, in the southeast region of Turkey. Anemia was found in 142 (7.8%) children in the 6-11 years of age group, and in 16 (1.5%) in the 12-16 years of age group; in total, in 158 (5.4%) children. Causes were iron deficiency in 93 (58.9%) children, β-thalassemia heterozygosity in 10 (6.3%) children, chronic disease that causes anemia of inflammation in 30 (19.0%) children, and intestinal parasitic infections in 17 (10.8%) children. In eight (5.1%) children, the cause of anemia could not be determined. The study’s results showed that iron deficiency anemia and chronic and parasitic disease are important problems in schoolchildren of Şanlıurfa, while β-thalassemia and hemoglobinopathies have less importance.